NqA: An R-based algorithm for the normalization and analysis of microRNA quantitative real-time polymerase chain reaction data - Verderio, Paolo; Bottelli, Stefano; Ciniselli, Chiara Maura; Pierotti, Marco Alessandro; Gariboldi, Manuela; Pizzamiglio, Sara (Analytical biochemistry, 2014)
In this note, we propose an R function named NqA (Normalization qPCR Array, where qPCR is quantitative real-time polymerase chain reaction) suitable for the identification of a set of microRNAs (miRNAs) to be used for data normalization in view of subsequent validation studies with qPCR data. NqA is available through the website of the Fondazione IRCCS Istituto Nazionale dei Tumori of Milan (http://www.istitutotumori.mi.it/modules.php?name=Content&pa=showpage&pid=812) with a dedicated user’s guide. We applied our function on a qPCR dataset downloaded from the Gene Expression Omnibus (GEO) database. Results show that NqA provides a functional subset of reference miRNAs and a set of promising significantly modulated miRNAs for subsequent validation studies.